On the Smoothness of the Invariant Torus of a Countable System of Difference Equations with Parameters - Marchuk, N. A.; Teplinsky, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We establish sufficient conditions for the differentiability of the invariant torus of a countable system of linear difference equations defined on a finite-dimensional torus with respect to an angular variable and the parameter of the original system of equations.